Privatization : principles and practice - International Finance CorporationThe (Washintong, D.C. : The World Bank, 1995)
This book attempts to encourage growth of productive private enterprise in developing countries and over the last decade privatization has become one of our staples
IFC lessons of experience series
Includes bibliography
mf 22/01/2019
Loans
Keywords: World Bank; privatization; Washington, D.C